How artificial intelligence revolutionizes the world of multiple myeloma - Romero, Martha; Mosquera Orgueira, Adrián; Mejía Saldarriaga, Mateo (Frontiers in Hematology, 2024)
Multiple myeloma is the second most frequent hematologic malignancy worldwide with high morbidity and mortality. Although it is considered an incurable disease, the enhanced understanding of this neoplasm has led to new treatments, translating in improved patients' life expectancy. A large volume of data has been generated through different studies in the setting of clinical trials, prospective registries, and real-world cohorts, which have incorporated laboratory tests, flow cytometry, molecular markers, cytogenetics, diagnostic images, and therapy to routine clinical practice.In this review, we described how these data can be processed and analyzed with different models of artificial intelligence, aiming to improve accuracy and translate into clinical benefit. Allowing a substantial improvement in early diagnosis and response evaluation, faster analyses, reducing laborintensive prone to operator bias, as well as a capacity to evaluate a greater number of parameters that provide more precise information.Furthermore, we showed how artificial intelligence has allowed the development of integrated models that predict response to therapy, the probability to achieve undetectable measurable residual disease, progression free survival, and overall survival leading to better clinical decisions, and with the potential to inform on personalized therapy, that could improve patients' outcomes.Overall, artificial intelligence has the potential to revolutionize multiple myeloma care, being necessary to validate in prospective clinical cohorts and developing models to incorporate into routine daily clinical practice.